Mir-20a regulates in vitro mineralization and BMP signaling pathway by targeting BMP-2 transcript in fish - Tiago, Daniel (2014)
MicroRNAs (miRNAs) are important regulators of vertebrate development but their role during skeletogenesis remains unknown. In this regard, we investigated the mineralogenic activity of miR-20a, a miRNA associated with osteogenesis, in fish bone-derived cells. Expression of miR-20a was up-regulated during differentiation and its overexpression inhibited mineralization, suggesting a role in fish tissue calcification. In this regard, a conserved miR-20a binding site was identified in bone morphogenetic protein 2 (BMP-2) 30UTR and its functionality was evidenced through luciferase assays, and further confirmed by western-blot and qPCR. Type II BMP receptor (BMPR2) is also targeted by miR-20a in mammalian systems and evidence was collected for the presence of a binding site in fish sequences. We propose that miR-20a is a regulator of BMP pathway through specific action on BMP-2 and possibly BMPR2. Overexpression of miR-20a was also shown to up-regulate matrix Gla protein (MGP) transcript, a physiological inhibitor of calcification previously found to form a complex with BMP-2. We propose that MGP may play a role in the anti-mineralogenic effect promoted by miR-20a by decreasing availability of BMP-2. This study gives new insights into miRNA-mediated regulation of BMP-2, and sheds light into the potential role of miR-20a as a regulator of skeletogenesis.